2016
DOI: 10.1038/srep20863
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Transcranial Sonography of the Substantia Nigra in Parkinson’s disease: A Systematic Review and Meta-analysis

Abstract: A large number of articles have reported substantia nigra hyperechogenicity in Parkinson’s disease (PD) and have assessed the diagnostic accuracy of transcranial sonography (TCS); however, the conclusions are discrepant. Consequently, this systematic review and meta-analysis aims to consolidate the available observational studies and provide a comprehensive evaluation of the clinical utility of TCS in PD. Totally, 31 studies containing 4,386 participants from 13 countries were included. A random effects model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 54 publications
1
31
1
2
Order By: Relevance
“…Overall, our meta-analysis revealed that TCS has good sensitivity (84%) and specificity (85%) in the detection of PD when SN+ is the reference standard for PD. In the subgroup analysis, our meta-analysis indicated that TCS has good sensitivity (85%) and specificity (89%) in the differentiation of PD patients from normal controls, which is consistent with the result reported by Li et al (2016) (sensitivity = 83% and specificity = 87%). In addition, TCS had good sensitivity (82%) and moderate specificity (74%) in the differentiation of PD from other parkinsonism symptoms.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Overall, our meta-analysis revealed that TCS has good sensitivity (84%) and specificity (85%) in the detection of PD when SN+ is the reference standard for PD. In the subgroup analysis, our meta-analysis indicated that TCS has good sensitivity (85%) and specificity (89%) in the differentiation of PD patients from normal controls, which is consistent with the result reported by Li et al (2016) (sensitivity = 83% and specificity = 87%). In addition, TCS had good sensitivity (82%) and moderate specificity (74%) in the differentiation of PD from other parkinsonism symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, TCS had good sensitivity (82%) and moderate specificity (74%) in the differentiation of PD from other parkinsonism symptoms. Previous metaanalyses by Li et al (2016) reported only the analytic accuracy of TCS in differentiating PD patients from normal controls, whereas in this meta-analysis, we analyzed the accuracy of TCS in differentiating PD from both normal controls and controls with other parkinsonism symptoms. For all meta-analyses, heterogeneity is a potential problem when interpreting results.…”
Section: Discussionmentioning
confidence: 99%
“…MRI studies have shown very similar patterns of microstructural damage or altered diffusion patterns in RBD and PD (Barber, Klein, Mackay, & Hu, ; Heim, Krismer, De Marzi, & Seppi, ; Pyatigorskaya et al., ). Transcranial sonography (TCS) identifies increased echogenicity in the area of the substantia nigra in around 10% healthy controls, 90% of PD and 36%–50% RBD (Iranzo et al., ; Li, He, Liu, & Chen, ). Dopamine transporter single photon emission tomography (DAT‐SPECT) in RBD cohorts point towards this test's utility as a marker of impending conversion to overt Parkinsonism (Högl et al., ).…”
Section: Rem Sleep Behaviour Disordermentioning
confidence: 99%
“…The TCS parameters have been standardized in diverse ultrasound models 12 , replicated with good inter-investigator reproducibility 7,13 , and reproduced in distinct populations 14,15 . The association between substantia nigra (SN) hyperechogenicity detected by TCS and the subsequent development of PD 8,16,17 suggests that TCS might enable early diagnosis 16,18 .…”
Section: Introductionmentioning
confidence: 99%